Valvular Disease Begets Valvular Disease - Diana DeCampos, MD; Rogério Teixeira, MD, PhD; João Lopes, MD; Carolina Saleiro, MD; Lino Gonçalves, MD, PhD (JACC: Case Reports, 2020)
In acute severe aortic regurgitation, an inversion of pressure gradient from the left ventricle to the left atrium causes the classical sign of end-diastolic mitral regurgitation. Here we present a case of mid-diastolic mitral regurgitation in a 51-year-old man with severe aortic regurgitation secondary to infective endocarditis. (Level of Difficulty: Beginner.)